Modeling and Simulation of Factors Affecting the Development of Religious Tourism in Yazd Province - Ghasem Zarei; SeyedAli Naghavi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2023)
Adequate comprehension of the challenges and influential elements of the religious tourism sector is necessary for its positive development. In this regard, the present research was conducted to present a model that can simulate the development of religious tourism in Yazd province by considering the influential factors. A mixed method (qualitative and quantitative) was carried out in this study, and the research method was applied in terms of purpose and descriptive-analytical in terms of nature. The statistical population of this research included 12 theoretical and experimental experts. Questionnaires and interviews were used to collect data with non-random and purposeful sampling. In the qualitative section, the main and sub-categories of religious tourism development in Yazd province were identified using the thematic analysis method. Then, in the quantitative part, the identified influential factors were prioritized using the interpretive structural modeling (ISM) method. Finally, the criteria obtained from the qualitative research analysis were simulated using the agent-based modeling (ABM) method. Based on the research results, 35 initial codes, 12 sub-themes, and six main themes (religious tourism policies, economic, infrastructure, environmental empowerment, marketing, and cultural) were identified. Religious tourism policies were recognized as the most influential factor. Also, the results showed that at the end of the simulation period, the rate of religious tourism development in Yazd Province had reached 70%. Based on the findings of this study, it is recommended that tourism managers give particular attention to the influential factors that have been identified as having a significant impact on the development of religious tourism.IntroductionTourism is one of the most significant social and economic phenomena of the modern era, a valuable instrument for achieving development. Religious tourism is among the oldest forms of tourism and the largest market segment for travel. Today, this type of tourism has been able to place itself in the context of global tourism due to its unique structural and functional features, so its sphere of influence covers the whole world (Ghaffari et al., 2022). The vast country of Iran also has blessed places, shrines, and many holy places, which has made it favorable for the development of religious tourism. For this reason, knowing the capacities of the country's provinces is one of the most important influencing factors, among which is Yazd Province, which also has excellent potential for developing religious tourism. Therefore, according to the explanations presented above, this research aims to present a model that can simulate the development of religious tourism in Yazd Province by considering critical factors with a future research approach so that it can play a positive role in helping managers develop religious tourism.Literature ReviewOne of the main types of tourism created to travel to religious locations and fulfill religious obligations is religious tourism (Jamshidi et al., 2019). Religious tourism can be considered the most sustainable type of tourism because pilgrimage and religious tourism have their roots in religious beliefs, and in its specialized sense and beyond dependence on time and leisure, it is an essential factor of human geography in shaping travel, creating concentration and numerous cultural perspectives (Sharma et al., 2023).MethodologyThe current applied study employed a mixed methodology, combining qualitative and quantitative methods with a descriptive-analytical focus regarding the nature of the research. Managers of religious tourism and university faculty members made up the statistical population for this study. Due to the high number of experts in this field and the possibility of not knowing all theoretical experts (university faculty members) and practical experts (tourism managers) by the researcher, sampling by snowball method was continued until reaching theoretical saturation (N=12). Interviews and questionnaires were used to collect research data. The steps of this research are as follows:In the first step, the thematic analysis method, one of the qualitative methods, was used to identify the factors affecting the development of religious tourism in Yazd Province. In the second step, the ISM method was used to prioritize (level) the factors. In the third step, the development of religious tourism in Yazd Province was simulated.In the qualitative part of the research, the validity of the interview using the Q-sort method and its reliability using Cohen’s Kappa index were checked and confirmed. In the quantitative part of the research, the validity of the questionnaires using the relative content validity method and its reliability based on the test-retest method was evaluated and confirmed. Also, experts’ opinions were obtained during face-to-face interviews to check the validity of the Agent-Based Model.ResultsBased on the research results, 35 initial codes, 12 sub-themes, and six main themes were identified. Due to having the highest driving power and the lowest dependence power, the factor of religious tourism policies was placed in the fifth level of the ISM. It was recognized as the most influential factor. Also, the results showed that at the end of the simulation period, the rate of religious tourism development in Yazd Province was 70%.DiscussionAlthough with different degrees, all six factors are essential for the development of religious tourism, and their prioritization was only due to greater understanding and recognition of more influential factors. The results showed that at the end of the simulation period, the rate of religious tourism development in Yazd Province was 70%. Therefore, applying the discussed factors can influence the growth of tourism development and be used in the policies and actions of the relevant managers. In line with the results of the religious tourism development simulation, as a general policy, the managers of tourism organizations in Yazd Province should implement the current research model. In this way, the research model is implemented in a specific period, and its ability to improve the effectiveness of religious tourism development is measured if, in practice, the research model leads to development in future periods.ConclusionThe results of this study indicate that managers of religious tourism should incorporate the factors identified into their development plans and plan the long-term horizons of religious tourism around these factors. It is essential to remember that merely incorporating these elements into the plans for development is unlikely to result in complete development; as such, it is imperative to address this problem from a fundamental standpoint and consider other significant influencing factors that are occasionally external to the current system.